2020
DOI: 10.1007/s00710-020-00726-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal mineral assemblages of calcite and dolomite–analcime–pyrite in Permian lacustrine Lucaogou mudstones, eastern Junggar Basin, Northwest China

Abstract: The eastern Junggar Basin, controlled by continental extension (rift), was deposited by lacustrine dominated sediments during middle Permian Lucaogou period. An unusual porphyritic-like texture was observed in Lucaogou/Pingdiquan dark fine-grained organic-rich sediments in two sub-tectonic units in the basin. The “phenocrysts” are composed of two types of mineral assemblages. The first is a coarse euhedral calcite assemblage in the Jimusar Sag, and the second consists of dolomite, analcime, and pyrite in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 93 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…The above geochemical indicators of black shale samples from the Jiangjunmiao and Wucaiwan sections indicate that the physicochemical conditions, including salinity, palaeoclimate and redox, at the margin of the lake basin are similar to those in the centre of the lake basin that were reported previously (Bai et al, 2017). However, it is worth noting that in the centre of the lake basin sediments consist mainly of mixed carbonate‐siliciclastic shales (Li, Liu, Yang, Liu, & Niu, 2021), while along the margin of the basin sediments are dominated by terrigenous shales. Previous studies have shown that these mixed carbonate‐siliciclastic shales in the centre of the lake basin were closely related with synsedimentrary volcanic‐hydrothermal processes (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above geochemical indicators of black shale samples from the Jiangjunmiao and Wucaiwan sections indicate that the physicochemical conditions, including salinity, palaeoclimate and redox, at the margin of the lake basin are similar to those in the centre of the lake basin that were reported previously (Bai et al, 2017). However, it is worth noting that in the centre of the lake basin sediments consist mainly of mixed carbonate‐siliciclastic shales (Li, Liu, Yang, Liu, & Niu, 2021), while along the margin of the basin sediments are dominated by terrigenous shales. Previous studies have shown that these mixed carbonate‐siliciclastic shales in the centre of the lake basin were closely related with synsedimentrary volcanic‐hydrothermal processes (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that in the centre of the lake basin sediments consist mainly of mixed carbonate‐siliciclastic shales (Li, Liu, Yang, Liu, & Niu, 2021), while along the margin of the basin sediments are dominated by terrigenous shales. Previous studies have shown that these mixed carbonate‐siliciclastic shales in the centre of the lake basin were closely related with synsedimentrary volcanic‐hydrothermal processes (Li et al, 2021). Therefore, the prominent difference between the margin and the centre of the lake basin during the deposition of the Pingdiquan Formation is that the centre of the lake basin experienced intense synsedimentrary volcanic‐hydrothermal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing Fe and decreasing Mg contents from core to rim (Figures 6(b)-6(d), Table 1) indicated a substitution of Fe for Mg. Point 5 exhibits an abnormally high content of Ca (Figure 6(e), Table 1), indicating a possible limestone source. The irregular shape and distinct elemental compositions from the host 6 Geofluids dolomite indicated that it might be a "drop-stone" and was enclosed in the dolomite nodule during early diagenesis. The normalized elemental weight percentages of Ca, Mg, Fe, and the corresponding data precisions all show significant variations with different exposure times (Figure 7).…”
Section: Elementalmentioning
confidence: 99%
“…So far, massive dolostones are attributed to slow burial or hydrothermal dolomitization of calcite or aragonite precursors by Mg-rich fluids at temperatures of >100 °C [3,5,6]. In contrast, other studies have asserted that dolomites can form at low temperatures in pore waters during early diagenesis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, volcanic and hydrothermal activities in both modern and ancient records commonly show a strong relationship with microbial blooms (Fouquet, 1999; Xie et al ., 2010; Procesi et al ., 2019), and provide the elements (for example, CO 2 , Mg 2+ and Ca 2+ ), and modify the temperature and pH values that facilitate dolomite precipitation. Recently, some organic‐rich lacustrine dolomitic shales have been interpreted as products of volcanic eruption and hydrothermal exhalation, including: (i) the middle Permian Lucaogou Formation in the Santanghu and Junggar basins of north‐west China (Liu et al ., 2012; Jiao et al ., 2018a,b, 2020; Pan et al ., 2020; Li et al ., 2021; Zhang et al ., 2021); (ii) the Cretaceous Tengger Formation in the Erlian Basin of northern China (Yang et al ., 2020, 2021); and (iii) the Cretaceous Xiagou Formation in the Jiuquan Basin of south‐west China (Zheng et al ., 2006; Wen et al ., 2013). These studies describe complex depositional and diagenetic environments affected by volcanic–hydrothermal, authigenic and biological processes, which may have promoted the formation of primary dolomitic formation related to hydrothermal activities (Zheng et al ., 2006; Liu et al ., 2012; Yang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%